Intercontinental transport of tropospheric ozone: a study of its seasonal variability across the North Atlantic utilizing tropospheric ozone residuals and its relationship to the North Atlantic Oscillation - J. K. Creilson; J. K. Creilson; J. Fishman; A. E. Wozniak; A. E. Wozniak; A. E. Wozniak (Atmospheric Chemistry and Physics, 2003)
Using the empirically-corrected tropospheric ozone residual (TOR) technique, which utilizes coincident observations of total ozone from the Total Ozone Mapping Spectrometer (TOMS) and stratospheric ozone profiles from the Solar Backscattered Ultraviolet (SBUV) instruments, the seasonal and regional distribution of tropospheric ozone across the North Atlantic from 1979-2000 is examined. Its relationship to the North Atlantic Oscillation (NAO) is also analyzed as a possible transport mechanism across the North Atlantic. Monthly climatologies of tropospheric ozone for five different regions across the North Atlantic exhibit strong seasonality. The correlation between these monthly climatologies of the TOR and ozonesonde profiles at nearby sites in both eastern North America and western Europe are highly significant (R values of +0.98 and +0.96 respectively) and help to validate the use of satellite retrievals of tropospheric ozone. Distinct springtime interannual variability over North Atlantic Region 5 (eastern North Atlantic-western Europe) is particularly evident and exhibits similar variability to the positive phase of the NAO (R=+0.61, r=<0.01). Positive phases of the NAO are indicative of a stronger Bermuda-Azores high and a stronger Icelandic low and thus faster more zonal flow across the North Atlantic from west to east. This flow regime appears to be causing the transport of tropospheric ozone across the North Atlantic and onto Europe. The consequence of such transport is the impact on a downwind region's ability to meet their ozone attainment goals. This link between the positive phase of the NAO and increased tropospheric ozone over Region 5 could be an important tool for prediction of such pollution outbreaks.